Confusion is the first step towards understanding: Fixing the problems of E-learning in COVID-19 pandemic - Rehan, Madeeha; Khalid, Attika; Shaheen, Neelofar; Rehman, Humaira; Nasreen, Fariha (Journal of Rawalpindi Medical College, 2022)
Background: The COVID-19 pandemic forced institutions worldwide to adopt online learning, which opened a new era of challenges. Our research was designed to explore the effect of the pandemic on teaching and learning and identify the solutions to the problems based on participants’ perspectives. Methods: A qualitative study of the phenomenological design was conducted at a medical institute in Pakistan. The participants were selected using the purposive sampling technique. Semi-structured interviews were done which were later audio-recorded, transcribed, and subjected to manual thematic analysis. Credibility was ensured by using multiple data collection sources. Results: The 20 participants selected as interviewees were faculty with more than 5 years teaching experience in the medical institute and had gone through online teaching and learning during COVID-19 pandemic. The thematic analyses of the data generated six themes which were: 1. “I see what you mean”; Re-exploration of educational psychology, 2. Reorganization of curriculum, 3. Mentoring and coaching, 4. Technology: as ubiquities as oxygen, 5. Constructive feedback: a stimulus in pearl formation and 6. Turn the tables: fixing the problem. Conclusion: Online education has emerged as an important mechanism in delivering medical education to undergraduate medical students. Instead of shying away, efforts are needed to restructure the curricula, incorporating various online innovative teaching, and learning tools that are at par with the changing global demands of medical education. Keywords: E-learning, COVID-19, Challenges